2016
DOI: 10.3109/00016489.2016.1170876
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy of carboplatin and paclitaxel for advanced/metastatic salivary gland carcinoma patients: differences in responses by different pathological diagnoses

Abstract: Salivary gland cancer patients showed a moderate clinical response to the combination chemotherapy of carboplatin and paclitaxel. The objective response rates differed according to the pathological diagnoses, but there were no significant differences in prognoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 15 publications
5
34
1
Order By: Relevance
“…Overall, 6 of 10 patients receiving targeted therapy responded (4 PRs, 2 complete responses) and 2 patients achieved durable stable disease, comprising a response rate of 60% and disease control rate of 80%. These findings compared favorably with response rates previously described …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, 6 of 10 patients receiving targeted therapy responded (4 PRs, 2 complete responses) and 2 patients achieved durable stable disease, comprising a response rate of 60% and disease control rate of 80%. These findings compared favorably with response rates previously described …”
Section: Discussionsupporting
confidence: 86%
“…The approach to the incurable recurrent or metastatic patient is unclear, due to the great biological heterogeneity, which is highly histology‐dependent. Responses to systemic agents in unselected patients are generally modest . As randomized controlled studies are lacking, treatment selection in SGCs should be made on a more personalized approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective series of 18 patients with salivary duct carcinoma treated with carboplatin and paclitaxel, they had a median PFS of 6.5 months and median OS of 34.7 months. 16 In case of HER2-positive salivary duct carcinoma, which is observed in 21%-44% of patients with salivary duct carcinoma, trastuzumab may be added to chemotherapy. 17,18 In fact, trastuzumab-based treatment regimens have shown some promising responses.…”
Section: Discussionmentioning
confidence: 99%
“…5 In contrast, a recent retrospective review of patients with SDC suggested a benefit to treatment with combined carboplatin and paclitaxel. 6 Notably, this cohort of 18 patients was established from a retrospective review of >8 years of clinical records, which exemplifies the difficulty of performing robust prospective clinical trials in this type of cancer. A larger retrospective evaluation of 495 patients with SDC listed in the National Cancer Database indicated that surgical resection was superior to all other modalities, with insufficient data available to properly evaluate the role of conventional or targeted chemotherapies.…”
Section: Discussionmentioning
confidence: 99%